Legal theory of finance: Evidence from global financial networks - Prince Kwasi Sarpong; Jugjith Deodutt (Cogent Economics & Finance, 2019)
Katharina Pistor proposed the Legal Theory of Finance (LTF), based on the premise that finance is legally constructed. In this paper, we apply network science to provide empirical evidence from global financial networks (GFN) to support the argument of the LFT. Using data from the World Bank and IMF, we confirm that the GFN is indeed hierarchical. We also show that the depth of interconnectedness in the GFN is increasing. The United States is the most important node in the GFN but temporarily lost its position to the United Kingdom in 2008. This paper shows that the most important node in the GFN can temporarily shift during major global financial events. The United Kingdom has also lost its position in the GFN to Switzerland on several measures of centrality. We further confirm that there is no evidence of a flattening of the GFN. Although some emerging economies have improved significantly in terms of GDP and international reserves, these improvements have not reflected in their positions in the GFN. We propose that the approach to regulating the global financial system should focus on more stringent rules for the most central countries in the GFN. This could be more effective in ensuring stability in the global financial system.
Keywords: G15; G20; G29; 330; legal theory of finance; elasticity of law; network science; eigenvector centrality; betweenness centrality; degree centrality